A Catalyst‐Free Aqueous Synthesis of 2‐Amino‐7, 9‐dihydrothieno[3′, 2′:5, 6]pyrido[2, 3‐d]pyrimidine‐4, 6(3H, 5H)‐dione Derivatives. (18th April 2014) - Yao, Changsheng; Lu, Ting; Yu, Chenxia; Wang, Xiangshan; Li, Tuanjie
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>